REGRESSION ANALYSIS OF THE LEAD CONCENTRATION IN THE SOIL AT THE DISTANCE FROM THE LANDFILLS OF SOLID MUNICIPAL WASTE - Bereziuk, Oleg; Lemeshev, Myhailo; Dudar, Igor (Scientific Works of Vinnytsia National Technical University, 2023)
In recent years the total area of the solid municipal waste landfills and dumpsites, including the overloaded ones, which violate the norms of ecological safety and are the objects of intensive ecological loading, that may cause the pollution of the environment with chemical substances, contaminating soil, in particular with the lead has greatly increased. Determination of the regression dependence of lead concentration in the soil on the distance to solid municipal waste landfills is an important scientific-technical problem. Objective of the research is to determine the regressive dependence of lead concentration in the soil on the distance to solid municipal waste landfills. During the research the method of regressive analysis of the results of single-factor experiments and other pair dependences with the selection of the rational type of function from sixteen most widely spread variants by the criterion of maximum value of the correlation factor has been used. Regression was performed on the base of the linearizing transformations, which enable to reduce the nonlinear dependencein to linear one. Determination of the coefficients of the regression equations was carried out by means of the least squares method, applying the developed computer program "RegAnaliz", protected by the Certificate of the State registration of the rights to the copyright object. Adequate regressive power dependence of the lead concentration in the soil on the distance to solid municipal waste landfills was obtained, the dependence can be used for the determination of the level of chemical pollution of the soil with lead. Graphic interpretation of the lead concentration dependence in the soil on the distance to solid municipal waste landfill was constructed, it enables to illustrate this dependence and show the coincidence of the theoretical results with actual results on the level of 0.93493. It is established that the distance from the landfill of solid municipal waste, where the lead pollution of the soil does not exceed the background level(boundary of mild contamination area), is 526 m.